Effect of Fluoride on the Expression of type I Collagen Gene (COL1A1) in Skeletal Muscle of Rats - Aggarwal, Shashi; Rana, Nidhi (Asian Journal of Biological and Life Sciences, 2016)
The present study assessed the effect of high fluoride ingestion on expression levels of Type I Collagen gene (COL1A1) in skeletal muscle of rats. Thirty Wistar albino rats of both sexes were randomly assigned to three groups. The group I served as control and received 1ml double distilled water/kg/bodyweight/day orally for 40 days. The groups II and III were treated with 300 and 600 ppm of sodium fluoride in drinking respectively for the same period. The animals were sacrificed under ether anesthesia , skeletal muscle was excised and used for RT-PCR assay. Total RNA was isolated by homogenization in TRIzol, followed by the single step purification method . The RNA concentration was estimated using a spectrophotometer and an equal amount of total RNA was reverse-transcribed to synthesize single-stranded cDNA. Total cellular RNA was quantified using Nanodrop (USA). The RNA sample had A260/280 ratio between 1.78 and 1.88. Finally, gel electrophoresis with 1.5% agarose gel was used to detect the RNA. When the skeletal muscle mRNA was used for cDNA synthesis, a 136-bp product was produced using specific COL1A1 PCR primers. Controls lacking reverse transcriptase resulted in the production of no detectable PCR product. The expression level of collagen gene in skeletal muscle of fluoride exposed rats decreased as compared to the controls. Thus, investigating the effect of fluoride on the expression levels of COL1A1 of skeletal muscle provide basic data for further elucidating the molecular mechanisms of skeletal damage induced by fluoride toxicity.
Keywords: COL1A1 gene; Fluoride; Polymerase Chain Reaction; Rat skeletal muscle